THE IMPACT OF COMPUTER AND INFORMATION COMMUNICATION TECHNOLOGY LITERACY ON THE ACADEMIC ACHIEVEMENT OF MEDICAL AND DENTAL STUDENTS AT SHIRAZ UNIVERSITY OF MEDICAL SCIENCES - Mohagheghzadeh, M. S.,; Mortazavi, S. M. J.,; Ghasempour, M.; Jarideh, S. (European Scientific Journal, ESJ, 2014)
The internet, since its advent, has been well embraced and broadly used by students, faculty members and researchers as an information source, and as a tool for collaboration, learning and also a tool for the dissemination of research results. As such the internet is assumed to have a great effect on both the quality and quantity of research and education worldwide. In this regard, many studies have been conducted to know more about the applications and outcomes of the internet in educational fields. This article, in line with previous studies, was an attempt to investigate the impact of students’ computer and information communication technology (ICT) literacy on their academic achievement. According to the results, the Pearson correlation coefficient between students computer grades as a measure of their ICT skill and their grade point averages was (R=0.367, P<=0.01) which shows a positive and significant relationship between these two variables. Adopting a self-evaluation procedure, the students scored themselves low to average, regarding the application of numerous information services available to them on the campus. They additionally self-evaluated their skills in using Microsoft Office products as good. Their knowledge and skill with regard to internet and email services was ranked as very good. The students spent nearly 3 hours a day on different internet activities as follows: internet search (60 minutes), social networks (45 minutes) and electronic mails (30 minutes).